Martha C. Nussbaum. The Monarchy of Fear, A philosophical look at the current political crisis. Bogotá: Editorial Planeta Colombia, 2019 - López González, Rosendo; Ramírez-Valencia, Astrid (Visión electrónica, 2020)
Martha C. Nussbaum. The Monarchy of Fear, A philosophical look at the current political crisis. Bogotá: Editorial Planeta Colombia, 2019